Preparation method of high-dispersion nickel nanoparticles and hydrogen storage catalysis application of high-dispersion nickel nanoparticles
Through the solvent-thermal reaction and reduction method, a highly dispersed nickel nanoparticles were prepared by using a viscous solvent and reducing reaction conditions, which solved the problem of insufficient hydrogen storage performance caused by catalyst agglomeration and large particle size, and achieved efficient catalytic effect and low-cost process.
Patent Information
- Application Number
- CN202411554459.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Severe agglomeration occurs when the catalyst is doped, and the impact on MgH2 hydrogen storage performance when the catalyst particle size is large cannot meet its application requirements.
By solvothermal reaction and reduction methods, viscous solvents such as oleic acid and 1,2-propanediol are used to reduce the agglomeration of Ni metal element, achieving uniform dispersion of the catalyst, and reducing the size of the catalyst by reducing the reaction time and temperature.
The preparation of highly dispersed nickel nanoparticles is achieved, the stability and catalytic activity of the catalyst are improved, the hydrogen storage performance of MgH2 is enhanced, and the technology and cost of the preparation process are reduced.
Smart Images

Figure CN119501056A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a controllable preparation method of highly dispersed nickel nanoparticles and hydrogen storage catalytic application thereof. Background Art
[0002] At present, among solid-state hydrogen storage materials, magnesium hydride MgH2 has a high hydrogen storage capacity of 7.6wt%, and the raw material Mg content is rich and the cost is low. However, MgH2 has the problems of high thermal stability and slow kinetic performance. In order to solve the above problems, the catalyst doping method can be used for improvement. Among them, transition metals Fe, Co, Ni and Cu have been shown to play an important role in improving the hydrogen storage performance of MgH2. MgH2 doped with Ni catalyst exhibits excellent hydrogen storage performance. Studies have found that metal Ni particles can easily react with Mg to produce Mg2Ni compounds during the dehydrogenation process. The in-situ generated Mg2Ni is converted into Mg2NiH4 in the subsequent rehydrogenation process, acting as a hydrogen pump. However, there are two technical problems with the method of doping catalyst Ni:
[0003] 1. Serious agglomeration will occur when the catalyst is doped;
[0004] 2. When the catalyst particle size is large, the impact on the hydrogen storage performance of MgH2 cannot meet its application requirements.
[0005] To solve the agglomeration problem, the dispersion of the catalyst can be improved by adding a suitable supporting material as a carrier. The current classification of supporting material types mainly includes: carbon materials, metal organic frameworks, and metal compounds. For example, document 1 (M. Chen, XZ Xiao, M. Zhang, et al., Excellent synergistic catalytic mechanism of insituformd nanosized Mg2Ni and multiple valence titanium for improved hydrogen desorption properties of magnesium hydride, Int. J. Hydrogen Energy, 44 (2019), No. 3, p. 1750.) studied the hydrogen storage performance of the MgH2-Ni / TiO2 system. By loading Ni on TiO2, the dehydrogenation performance of MgH2 was effectively improved, but it was found that metal Ni particles would also agglomerate on the carrier. The reason is that some carrier materials themselves are also prone to agglomeration.
[0006] Studies have shown that there are many ways to reduce the size of catalyst particles, among which ball milling is considered to be a cheap and suitable large-scale method. For example, in the existing literature 2 (D. Rahmalina, RA Rahman, A. Suwandi, and Ismail, The recent development on MgH2 system by 16wt.%nickel addition and particle size reduction through ball milling: A noticeable hydrogen capacityup to 5wt.%at low temperature and pressure, Int. J. Hydrogen Energy, 45 (2020), No. 53, p. 29046.), the size of Ni particles is reduced by ball milling to improve the thermodynamic and kinetic properties of MgH2. However, the optimal size of Ni and its size effect on dehydrogenation / rehydrogenation performance remain unclear. Summary of the invention
[0007] The purpose of the present invention is to provide a controllable preparation method of highly dispersed nickel nanoparticles and their hydrogen storage catalytic application.
[0008] Based on the research and analysis of the above technical background, the following conclusions can be drawn:
[0009] 1. Serious agglomeration will occur when the catalyst is doped;
[0010] 2. When the catalyst particle size is large, the effect on the hydrogen storage performance of MgH2 cannot meet its application requirements;
[0011] 3. The current method for preparing nano-scale metal elements is complex, costly and has a low yield.
[0012] In view of the technical problems existing in the prior art, the present invention adopts a solvent thermal reaction and a reduction method to prepare highly dispersed nickel nanoparticles as a hydrogen storage catalyst to achieve the following invention objectives:
[0013] 1. By adding viscous solvents such as oleic acid and 1,2-propylene glycol, the agglomeration of Ni metal elements during the reaction is reduced, thus achieving a uniform dispersion of the catalyst;
[0014] 2. Reduce the size of the catalyst by reducing the reaction time and temperature while reducing the preparation process technology and cost.
[0015] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0016] A highly dispersed nickel nanoparticle is prepared by using sodium hydroxide, nickel acetate tetrahydrate, oleic acid, PVP and 1,2-propylene glycol as raw materials through solvent thermal reaction and reduction; the obtained highly dispersed nickel nanoparticle has uniform size and stable structure, and the average particle size is 3nm.
[0017] A method for preparing highly dispersed nickel nanoparticles comprises the following steps: mixing sodium hydroxide, nickel acetate tetrahydrate, oleic acid, PVP and 1,2-propylene glycol, heating and stirring under an argon atmosphere to obtain a solution A; then, adding a quantitative amount of hydrazine hydrate to perform a reduction reaction on the solution A; after the reaction is completed, centrifugally washing the reaction product with deionized water and anhydrous ethanol as centrifugal washing liquids under certain conditions; and finally, vacuum drying under certain conditions to obtain highly dispersed nickel nanoparticles.
[0018] In the method, the molar ratio of sodium hydroxide to nickel acetate tetrahydrate is 50:1; and the volume ratio of 1,2-propylene glycol to oleic acid is 30:1.
[0019] In the method, the conditions of the solvent thermal reaction are: the reaction temperature is 180-200°C and the reaction time is 20-24h;
[0020] In the method, the centrifugal washing conditions are: the centrifugal washing speed is 5000-7000 rpm, and the centrifugal washing time is 3-5 minutes; the drying conditions are: the drying temperature is 60-80° C., and the drying time is 10-12 hours.
[0021] A preparation method of a magnesium hydride composite hydrogen storage material based on highly dispersed nickel nanoparticles, wherein MgH2 and nickel meet a certain mass ratio and are ball-milled under certain conditions to obtain a magnesium hydride composite hydrogen storage material based on highly dispersed nickel nanoparticles, referred to as MgH2-nano Ni;
[0022] The mass ratio of MgH2 to highly dispersed nickel nanoparticles is 47:3;
[0023] The ball milling conditions are as follows: the ball milling speed is 450 rpm, the ball milling time is 4 h, and the ball-to-material ratio is 60:1.
[0024] The initial dehydrogenation temperature of the obtained MgH2-nano Ni is 190°C; under the conditions of a dehydrogenation temperature of 325°C and a dehydrogenation time of 300s, the dehydrogenation amount is 6.3-6.4wt%; under the conditions of a hydrogen absorption temperature of 125°C and a hydrogen absorption time of 300s, the hydrogen absorption amount is 6.1-6.2wt%.
[0025] The technical effects of the present invention have been tested and the specific contents are as follows:
[0026] The invention has been tested by XRD and found that the diffraction peak of the highly dispersed nickel nanoparticles is consistent with the characteristic peak of standard Ni: the result proves the successful preparation of highly dispersed nickel nanoparticles;
[0027] According to TEM test, the size of the metal element Ni is about 3-5 nm.
[0028] Dehydrogenation detection of the present invention shows that when the doping amount of the highly dispersed nickel nanoparticles is 4-8wt%, the initial dehydrogenation temperature is 188-192°C, and the dehydrogenation amount is 6.8-7.1wt%.
[0029] In summary: The successfully prepared highly dispersed nickel nanoparticles can have good catalytic activity towards magnesium hydride.
[0030] Compared with the prior art, the present invention has the following advantages:
[0031] 1. The addition of viscous solvent can effectively inhibit the agglomeration of metal particles and improve their catalytic activity and stability;
[0032] 2. Highly dispersed nickel nanoparticles have stable properties and structures and are not easily destroyed. Their small particle size provides more catalytic active sites, thereby increasing the catalytic efficiency of the catalyst.
[0033] 3. The raw materials used are commercially available, the process is simple, and low energy consumption and pollution are achieved.
[0034] Therefore, compared with the prior art, the present invention has better MgH2 hydrogen storage catalytic performance, improves the stability and catalytic activity of the catalyst, and has broad application prospects in the fields of hydrogen storage materials, fuel cells, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the XRD pattern of the highly dispersed nickel nanoparticles prepared in Example 1;
[0036] Figure 2 TEM image of the highly dispersed nickel nanoparticles prepared in Example 1;
[0037] Figure 3 HAADF and EDS images of the highly dispersed nickel nanoparticles prepared in Example 1;
[0038] Figure 4 TPD graphs of MgH2-4wt% nano Ni, MgH2-6wt% nano Ni and MgH2-8wt% nano Ni prepared in Example 1, Comparative Example 1 and Comparative Example 2;
[0039] Figure 5This is the hydrogen release diagram of the prepared MgH2-6wt% nano Ni at 325°C in Example 1;
[0040] Figure 6 This is the hydrogen absorption diagram of MgH2-6wt% nano Ni prepared in Example 1 at 125°C;
[0041] Figure 7 This is the hydrogen release diagram of pure ball-milled magnesium hydride at 275℃, 300℃, and 325℃. DETAILED DESCRIPTION
[0042] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0043] Example 1
[0044] A method for preparing highly dispersed nickel nanoparticles:
[0045] 1.8g of sodium hydroxide, 0.2241g of nickel acetate tetrahydrate, 2.05g of oleic acid, 0.5g of PVP, and 150ml of 1,2-propylene glycol are mixed under an argon atmosphere and heated with stirring to obtain solution A; then, 5ml of hydrazine hydrate is added to perform a reduction reaction on solution A. After the reaction is completed, the product obtained by the reaction is centrifugally washed with deionized water and anhydrous ethanol respectively under certain conditions, and finally, vacuum dried under certain conditions to obtain highly dispersed nickel nanoparticles.
[0046] In order to prove the composition of highly dispersed nickel nanoparticles, XRD test was carried out. The test results are shown in Figure 1 As shown, the diffraction peak of the highly dispersed nickel nanoparticles is consistent with the characteristic peak of Ni. The test results show that the composition of the highly dispersed nickel nanoparticles is Ni.
[0047] In order to verify the microstructure of highly dispersed nickel nanoparticles, TEM test was performed. The test results are shown in Figure 2 As shown, a nanocatalyst with small particle size and uniform distribution was prepared.
[0048] In order to demonstrate the effect of highly dispersed nickel nanoparticles as MgH2 catalysts, magnesium hydride composite hydrogen storage materials based on highly dispersed nickel nanoparticles were prepared.
[0049] A method for preparing a magnesium hydride composite hydrogen storage material based on highly dispersed nickel nanoparticles, wherein the mass ratio of MgH2 to highly dispersed nickel nanoparticles is 47:3, ball milling is performed under the conditions of a ball milling speed of 450 rpm, a ball milling time of 4 hours, and a ball-to-material ratio of 60:1, to obtain a magnesium hydride composite hydrogen storage material based on highly dispersed nickel nanoparticles, referred to as MgH2-nano Ni. The MgH2-nano Ni obtained in specific embodiment 1 is named MgH2-6wt% nano Ni.
[0050] In order to demonstrate the hydrogen desorption performance of MgH2-6wt% nano Ni, TPD test and PCT test were performed; for comparison, TPD test and PCT test were also performed on pure ball-milled MgH2.
[0051] The TPD test results of pure ball-milled MgH2 are as follows Figure 4 As shown, the initial hydrogen release temperature is 250°C;
[0052] The TPD test results of MgH2-6wt% nanoNi are as follows Figure 4 As shown, the initial hydrogen release temperature is 190°C;
[0053] Therefore, the TPD test results show that the addition of highly dispersed nickel nanoparticles significantly reduces the onset hydrogen desorption temperature of MgH2 by 60°C.
[0054] The PCT test results of MgH2-6wt% nano Ni are as follows Figure 6 As shown, at 325°C, it only takes 500s to reach the maximum hydrogen release; under the conditions of hydrogen absorption temperature of 125°C and hydrogen absorption time of 300s, the hydrogen absorption amount is 6.1-6.2wt%
[0055] The PCT test results show that the addition of highly dispersed nickel nanoparticles greatly improves the hydrogen desorption kinetics.
[0056] In order to demonstrate the effect of the addition amount of highly dispersed nickel nanoparticles on the performance, comparative examples 1 and 2 are provided, which are MgH2 composite materials based on highly dispersed nickel nanoparticles with the addition amounts of highly dispersed nickel nanoparticles being 4 wt % and 8 wt %, respectively.
[0057] Comparative Example 1
[0058] A method for preparing a magnesium hydride composite hydrogen storage material with a 4wt% addition amount of highly dispersed nickel nanoparticles, wherein the steps not specifically described are the same as those in Example 1, except that when preparing the composite hydrogen storage material, the mass ratio of MgH2 to the highly dispersed nickel nanoparticles is 24:1, and the obtained material is named MgH2-4wt% nano Ni.
[0059] The TPD performance test results of MgH2-4wt% nano Ni are as follows Figure 3 As shown, the initial hydrogen desorption temperature is 192°C and the hydrogen desorption amount is 7.1 wt%.
[0060] By comparison with Example 1, it can be seen that the addition of MgH2-6wt% nano Ni can reduce the initial dehydrogenation temperature of MgH2 by 65°C. The reason is that although the metal Ni particles are easily reacted with Mg to produce Mg2Ni compounds during the dehydrogenation process, the in-situ generated Mg2Ni is converted into Mg2NiH4 in the subsequent rehydrogenation process, acting as a hydrogen pump, and ultimately improving the catalytic effect and making the initial dehydrogenation temperature lower, the concentration of the hydrogen pump decreases due to the reduction in the amount of additive added, resulting in fewer reaction sites, so the catalytic performance is not significantly improved.
[0061] Comparative Example 2
[0062] A method for preparing a magnesium hydride composite hydrogen storage material with an addition amount of highly dispersed nickel particles of 8wt%, wherein the steps not specifically described are the same as those in Example 1, except that when preparing the composite hydrogen storage material, the mass ratio of MgH2 to highly dispersed nickel nanoparticles is 23:3, and the obtained material is named MgH2-8wt% nano Ni.
[0063] The TPD performance test results of MgH2-8wt% nano Ni are as follows Figure 3 As shown, the initial hydrogen desorption temperature is 188°C and the hydrogen desorption amount is 6.8wt%.
[0064] By comparing with Comparative Example 1, it can be seen that with the addition of MgH2-8wt% nano Ni, as the amount of additive increases, the number of reaction sites increases, so the initial hydrogen desorption temperature is lower than 192°C of MgH2-4wt% nano Ni, but as the by-product generation increases, the amount of hydrogen desorption decreases. The results show that the catalytic performance of MgH2-8wt% nano Ni is higher than that of MgH2-4wt% nano Ni.
[0065] The following conclusions can be drawn from the above examples:
[0066] By adding highly dispersed nickel nanoparticles, the MgH2-nano Ni system is constructed, the contact sites between the catalyst and MgH2 are increased, and the catalytic effect is improved, so that the initial dehydrogenation temperature is lower. With the increase of additives, the channels for electron transmission increase, the reaction sites also increase, and the catalytic effect is also improved, but at the same time, the reaction by-products increase, reducing the maximum dehydrogenation amount. The results show that under different addition amounts, compared with MgH2-4wt% nano Ni reducing the initial dehydrogenation temperature of MgH2 to 192°C, and MgH2-8wt% nano Ni reducing the initial dehydrogenation temperature of MgH2 to 188°C, MgH2-6wt% nano Ni in Example 1 can reduce the initial temperature to 190°C. However, considering the initial dehydrogenation temperature and the maximum dehydrogenation amount, MgH2-6wt% nano Ni is selected as its main research system.
Claims
1. A highly dispersed nickel nanoparticle, characterized in that: The obtained highly dispersed nickel nanoparticles have uniform size and stable structure, and the average particle size is 3nm.
2. A method for preparing highly dispersed nickel nanoparticles, characterized in that: Sodium hydroxide, nickel acetate tetrahydrate, oleic acid, PVP and 1,2-propylene glycol are mixed under argon atmosphere, heated and stirred to obtain solution A; then, a quantitative amount of hydrazine hydrate is added to perform a reduction reaction on solution A, and after the reaction is completed, the reaction product is centrifugally washed with deionized water and anhydrous ethanol respectively under certain conditions, and finally, vacuum dried under certain conditions to obtain highly dispersed nickel nanoparticles.
3. The method for preparing highly dispersed nickel nanoparticles according to claim 2, characterized in that: The molar ratio of sodium hydroxide to nickel acetate tetrahydrate is 50:1; the volume ratio of 1,2-propylene glycol to oleic acid is 30:
1.
4. The method for preparing highly dispersed nickel nanoparticles according to claim 2, characterized in that: The conditions for the solvent thermal reaction are: reaction temperature of 116-120°C, reaction time of 2-3h; the conditions for the centrifugal washing are: centrifugal washing speed of 5000-7000rpm, centrifugal washing time of 3-5min; the conditions for drying are: drying temperature of 60-80°C, drying time of 10-12h.
5. A method for preparing a magnesium hydride composite hydrogen storage material based on highly dispersed nickel nanoparticles, characterized in that: By ball milling MgH2 and the highly dispersed nickel nanoparticles described in claim 1 at a certain mass ratio under certain conditions, a magnesium hydride composite hydrogen storage material based on highly dispersed nickel nanoparticles, referred to as MgH2-nano Ni, can be obtained.
6. The method for preparing the composite hydrogen storage material according to claim 5, characterized in that: The mass ratio of the MgH2 to the highly dispersed nickel nanoparticles is 47:
3.
7. The method for preparing the composite hydrogen storage material according to claim 5, characterized in that: The ball milling conditions are as follows: the ball milling speed is 450 rpm, the ball milling time is 4 h, and the ball-to-material ratio is 60:
1.
8. The method for preparing the composite hydrogen storage material according to claim 6, characterized in that: The initial dehydrogenation temperature of the obtained MgH2-nano Ni is 190°C; under the conditions of a dehydrogenation temperature of 325°C and a dehydrogenation time of 300s, the dehydrogenation amount is 6.3-6.4wt%; under the conditions of a hydrogen absorption temperature of 125°C and a hydrogen absorption time of 300s, the hydrogen absorption amount is 6.1-6.2wt%.
Citation Information
Patent Citations
Magnesium hydride hydrogen storage material based on Ni-coated TiO2 as well as preparation method and application of magnesium hydride hydrogen storage material
CN116588898A
NANO magnesium hydride and in-situ preparation method thereof
US20210198107A1